A variant of valence splicing systems: weighted splicing systems - Sarmin, Nor Haniza
In this paper we introduce a new variant of splicing systems, called weighted splicing systems, and establish basic properties of language families generated by this type of splicing systems. We show that a simple extension of splicing systems with weights increase the computational power of splicing systems with finite components.